2020
DOI: 10.3389/fnins.2020.559314
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Glutamate and GABA Detection in Pons and Thalamus at 3T and 7T by Proton Magnetic Resonance Spectroscopy

Abstract: Glutamate detection in pons and thalamus using proton magnetic resonance spectroscopy (1 H-MRS) after an intervention is of interest for studying various brain disorders. However, 1 H-MRS in these brain regions is challenging and time-consuming, especially in longitudinal study designs. 1 H-MRS of more cortical structures at the ultrahigh magnetic field strength of 7T yields an improved spectral output, including separation of the glutamate signal from the glutamine signal, in a shorter and more feasible scan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…In the current study, we investigated Glx, which represents the combined concentration estimate of glutamate and glutamine, as the signals of these two metabolites are inseparable at 3 Tesla ( Deelchand et al, 2014 , Younis et al, 2020b ). However, majority of the combined concentration (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, we investigated Glx, which represents the combined concentration estimate of glutamate and glutamine, as the signals of these two metabolites are inseparable at 3 Tesla ( Deelchand et al, 2014 , Younis et al, 2020b ). However, majority of the combined concentration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated measurements during the course of a migraine attack may elucidate if alterations in the glutamate levels appear closer to an impending attack, and/or in the early stages of an attack. Future pontine investigation in migraine may be expanded by adding measurement of the major inhibitory neurotransmitter, gamma-aminobutyric acid (GABA), possibly at increased magnetic field strengths ( Younis et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has established a robust 7T protocol for glutamate MRS at our 7T MR system and validated the protocol in a cohort on healthy individuals in a study on normal cognitive aging ( 71 , 72 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“…18 Comparisons of spectroscopy at lower field strengths such as 1.5T and 3T versus higher field strengths such as 7T to date have indicated that 7T is associated with substantial gains in SNR and more limited increases in spatial resolution, 19 better spectral separation and therefore additional tumor-specific metabolite information, 20 superior quantification of metabolites with small signals such as Gln, 21 and reduced Cramér-Rao lower bound (CRLB) values. [22][23][24][25] CRLB is a measure of the precision of an estimate, similar to an SD, which is used particularly with LCModel (http://www. lcmodel.com/).…”
mentioning
confidence: 99%